Trafficking and localization of Golgi-resident N-glycan processing enzymes in plants - Dünser, Kai; Schoberer, Jennifer (Frontiers in Plant Science, 2025)
Asparagine (N)-linked glycosylation is a fundamental co- and post-translational modification of proteins, playing a crucial role in protein folding, stability and function, protein-protein interactions, biotic and abiotic stress response as well as glycan-dependent quality control processes in the endoplasmic reticulum (ER). Protein N-glycosylation is initiated in the ER and continued in the Golgi apparatus by N-glycan-processing glycosyltransferases and glycosidases, which are compartmentalized in a highly organized manner reflecting their function in the sequential modification of glycans. Therefore, the precise localization of these enzymes is crucial for the optimal functioning of the glycosylation process and the secretory pathway and hence must be tightly regulated to maintain protein function, cellular health, and overall organismal development. Here, we highlight recent developments that contribute to a better understanding of the localization mechanisms of this important class of Golgi residents and discuss future directions to move the field forward.